Biological activity of the bryostatin analog Merle 23 on mouse epidermal cells and mouse skin. Issue 12 (9th February 2016) - Kelsey, Jessica S.; Cataisson, Christophe; Chen, Jinqiu; Herrmann, Michelle A.; Petersen, Mark E.; Baumann, David O.; McGowan, Kevin M.; Yuspa, Stuart H.; Keck, Gary E.; Blumberg, Peter M.
Abstract : Bryostatin 1, a complex macrocyclic lactone, is the subject of multiple clinical trials for cancer chemotherapy. Although bryostatin 1 biochemically functions like the classic mouse skin tumor promoter phorbol 12‐myristate 13‐acetate (PMA) to bind to and activate protein kinase C, paradoxically, it fails to induce many of the typical phorbol ester responses, including tumor promotion. Intense synthetic efforts are currently underway to develop simplified bryostatin analogs that preserve the critical functional features of bryostatin 1, including its lack of tumor promoting activity. The degree to which bryostatin analogs maintain the unique pattern of biological behavior of bryostatin 1 depends on the specific cellular system and the specific response. Merle 23 is a significantly simplified bryostatin analog that retains bryostatin like activity only to a limited extent. Here, we show that in mouse epidermal cells the activity of Merle 23 was either similar to bryostatin 1 or intermediate between bryostatin 1 and PMA, depending on the specific parameter examined. We then examined the hyperplastic and tumor promoting activity of Merle 23 on mouse skin. Merle 23 showed substantially reduced hyperplasia and was not tumor promoting at a dose comparable to that for PMA. These results suggest that there may be substantial flexibility in the design of bryostatin analogs that retain its lack of tumor promoting activity. © 2016 Wiley Periodicals, Inc.